PENINGKATAN KEMAMPUAN BERBICARA BAHASA INGGRIS MELALUI PELATIHAN ENGLISH FOR DAILY CONVERSATION BAGI REMAJA GPM IMANUEL KARANG PANJANG - Kakerissa, Wenda Marlin; Tuasela, Reinhard Glory (Universitas Pattimura, 2025)
This Community Service Program aimed to enhance the English-speaking skills of teenagers from SMTPI Jemaat GPM Imanuel Karang Panjang Ambon through the English for Daily Conversation training. Conducted over one month (October 2–30, 2025), the program consisted of nine sessions covering basic conversational topics such as introductions, family, hobbies, and expressing opinions. The training employed Communicative Language Teaching (CLT) and Task-Based Learning (TBL) approaches, combining interactive tasks and simple digital media. Results from the pre-test and post-test revealed significant improvement: no participants scored in the Fair or Poor categories; five reached Excellent and fifteen achieved Good. Beyond linguistic improvement, participants developed greater confidence and motivation to use English in daily life. Moreover, the program inspired the Church Council’s Education Division to consider implementing similar training in other subjects such as Chemistry, Mathematics, Physics, and Biology should God permit.